2017
DOI: 10.1002/pbc.26881
|View full text |Cite
|
Sign up to set email alerts
|

Deep vein thrombosis in pediatric patients

Abstract: Due to advances in caring for critically ill children and those with chronic diseases, rates of deep vein thrombosis (DVT) are increasing in children. Risk factors consist of central venous catheters, chronic medical conditions, thrombophilia, and various medications. Compression Doppler ultrasonography is the method most commonly used to diagnose DVT, and patients will usually present with pain and swelling of the affected limb. Anticoagulation via subcutaneous injection is the most common treatment regime fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 82 publications
0
29
1
1
Order By: Relevance
“…However, the risk of thrombotic events cannot be completely excluded as thrombosis in children is extremely rare. 12 Younger age is associated with greater odds of difficult IV access. 13 The desire to avoid CVL insertion and its complications may play a crucial role in the pediatrician's decision to delay ITI or to prefer emicizumab prophylaxis over standard ITI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the risk of thrombotic events cannot be completely excluded as thrombosis in children is extremely rare. 12 Younger age is associated with greater odds of difficult IV access. 13 The desire to avoid CVL insertion and its complications may play a crucial role in the pediatrician's decision to delay ITI or to prefer emicizumab prophylaxis over standard ITI.…”
Section: Discussionmentioning
confidence: 99%
“…Flow stagnation can result from sessile position of an individual, such as observed after surgery (especially an orthopedic one), in a bed-ridden position or even during long-haul flights. In pediatric patients, immobility for more than 72 h is also considered one of the main factors triggering DVT with each additional day of hospitalization increasing the risk by 3% [17] . Venous stasis increases also with age and it was observed that contrast material stays in the veins of elderly patients for up to 1 h after venography [18] .…”
Section: Stage 1: Blood Flow Stagnancy and Hypoxia Trigger Dvtmentioning
confidence: 99%
“…Interrupted flow usually results from immobilisation of the person for reasons such as bed-ridden position after surgery, paralysis or long-haul flights. For example, in paediatric patients, lack of movement exceeding 3 days is a recognised risk factor for venous thrombosis with each additional day of stay at hospital increasing the probability for DVT by 3% 7 . Blood flow in veins becomes slower 8 and valves stiffer with age which correlates with greatly increased prevalence of DVT in elderly people 9 .…”
mentioning
confidence: 99%